Métodos extrativos de mucilagem de semente de chia (Sálvia hispânica) para potencial uso em oftalmologia - Gusmão, Roberto da Silva [UNIFESP] (2017)
The mucilage are substances obtained some seeds, such as flax, chia, flax etc. These substances are rich in polysaccharides of high molecular weight and have essential oils, fatty acids and fiber. In oriental medicine, for example, chia seed has been used in various treatments. Among the treatments that chia seed is used in the control of cholesterol, obesity, food detoxification, increased gastric motility, reduction of cardiovascular risk, helps prevent premature aging and other benefits that are advocated in several published articles. The mucilage of plant origin are already established worldwide, mainly as vehicle laxative drugs. Thinking about the potential presented by the miraculous seed chia, the focus of this study is related to the choice of a cheap method of mucilage that produces seed with practical methods. It will be addressed in this work not only extractive methods for obtaining mucilage of chia seeds but will also be carried out physicochemical analyzes of mucilage obtained in the extraction process. Among the physicochemical studies in mucilage obtained include: pH, conductivity, sterility, heat resistance, osmolarity, viscosity and content, making it always the comparison with vehicles available in the market. Understand the physical and chemical characteristics of mucilage extracted from the seeds analyzed and understand its compatibility with the human body for potential use in medicine and especially in ophthalmology and the fundamental basis of this work.